2019
DOI: 10.1039/c9nj03648b
|View full text |Cite
|
Sign up to set email alerts
|

Pnictogen bonding with alkoxide cages: which pnictogen is best?

Abstract: Antimony cages have the best balance between strength and directionality compared to the other congeners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 60 publications
2
33
2
Order By: Relevance
“…The heavier pnictogen thiolate cages are more Lewis acidic as a result of increasing stereochemical inactivity of the lone pairs and the increasing polarity of the primary bonds. This is in line with ndings for the analogous alkoxide cages 36 and is in line with other experimental and computational ndings for pnictogen, chalcogen and halogen bonding in the +3, +2 and +1 oxidation states, respectively. [37][38][39][40][41][42] Computational study of the pnictogen bonding An oen suggested prerequisite for strong PnBs, following studies on halogen and chalcogen bonding, is the presence of large V max (maximum in the electrostatic potential energy surface calculated on a molecular surface at 0.001 au) 43,44 values associated with the electrophilic regions of the ESP surface.…”
Section: In Situ Encapsulation Of Guest Moleculessupporting
confidence: 91%
See 1 more Smart Citation
“…The heavier pnictogen thiolate cages are more Lewis acidic as a result of increasing stereochemical inactivity of the lone pairs and the increasing polarity of the primary bonds. This is in line with ndings for the analogous alkoxide cages 36 and is in line with other experimental and computational ndings for pnictogen, chalcogen and halogen bonding in the +3, +2 and +1 oxidation states, respectively. [37][38][39][40][41][42] Computational study of the pnictogen bonding An oen suggested prerequisite for strong PnBs, following studies on halogen and chalcogen bonding, is the presence of large V max (maximum in the electrostatic potential energy surface calculated on a molecular surface at 0.001 au) 43,44 values associated with the electrophilic regions of the ESP surface.…”
Section: In Situ Encapsulation Of Guest Moleculessupporting
confidence: 91%
“…The V max values, however, are intermediate to the analogous antimony alkoxide cage, which forms three pnictogen bonds, and the arsenic alkoxide cage, which only forms one in the solid state suggesting a diminished electrostatic contribution to the Sb/S pnictogen bonds. 36 Despite the lower V max values calculated for Sb-1 H, they are still considerably larger than those calculated for As-1 H (Fig. 5a) which further supports the use of the heavier pnictogens for stronger and more PnBs.…”
Section: In Situ Encapsulation Of Guest Moleculessupporting
confidence: 55%
“…While computational studies 9,20,23 and CSD analyses , 18 give consistent and forceful indications that PnB can work as a robust interaction to obtain co-crystals by design, very few cases have been reported where this potential has been explored. 24 In conclusion, results reported here increase the understanding of some key features of PnBs and may be useful in the design and realization of many other PnB driven recognition and self-assembly processes.…”
Section: Discussionmentioning
confidence: 61%
“…24 Experiments carried out on cocrystal 1 showed substantial changes of spectral parameters relative to pure SbF3 (Figure 4, Table 1). The quadrupolar coupling constants of 1 for 121 Sb and 123 Sb are 509.97 and 649.90 MHz, respectively, consistent with previous observations 24 that stronger and more directional PnBs at antimony are associated with smaller CQ values. It is also worth noting that the CQ values for 1 are comparable to those reported for the SbF3·urea co-crystal which has a chemical environment around the antimony atom somewhat similar to 1 as, in both adducts, the oxygen atom of two nearby electron density donor molecules engage in PnB formation.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation